2021
DOI: 10.3390/ma14185169
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Additives for Ground Improvement Utilizing Fine Powder of Waste Glass

Abstract: As a solidifying material for ground improvement using inorganic waste as a raw material, the authors have been developing an additive mixture of the fine powder of waste glass containing a large amount of silica generated during the production of glass cullet and an alkaline aid (heat-treating type of “Earth-Silica; ES” additive). Furthermore, a solidifying material that solidifies by mixing this additive with the fine powder of blast furnace slag, which is a by-product of steel production, is also being deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that ground subsidence can be prevented and that the impact of ground subsidence can be lessened by injecting a filler into the extraction holes of removed piles. In addition, it is considered desirable for the filler that is injected into the extraction holes of removed piles to aid in the development of strength so that local subsidence does not occur in the area around the filled holes [15][16][17]. Furthermore, it has also been clarified that the strength of the filler can be developed sooner by mixing sodium carbonate into it [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ground subsidence can be prevented and that the impact of ground subsidence can be lessened by injecting a filler into the extraction holes of removed piles. In addition, it is considered desirable for the filler that is injected into the extraction holes of removed piles to aid in the development of strength so that local subsidence does not occur in the area around the filled holes [15][16][17]. Furthermore, it has also been clarified that the strength of the filler can be developed sooner by mixing sodium carbonate into it [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is considered desirable for the filler that is injected into the extraction holes of removed piles to aid in the development of strength so that local subsidence does not occur in the area around the filled holes [15][16][17]. Furthermore, it has also been clarified that the strength of the filler can be developed sooner by mixing sodium carbonate into it [15][16][17].…”
Section: Introductionmentioning
confidence: 99%